2015
DOI: 10.1074/jbc.m115.655076
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding Cassette Transporter A7 (ABCA7) Loss of Function Alters Alzheimer Amyloid Processing

Abstract: Background:The ATP-binding cassette transporter A7 (ABCA7) is a risk factor for sporadic Alzheimer disease (AD). Results: Loss of ABCA7 promoted A␤ processing and pathology in cell culture and AD mouse models. Conclusion: Altered ABCA7 function may contribute to AD by impacting A␤ production in addition to clearance. Significance: AD-related risk factors may contribute to disease progression through multiple pathways.The ATP-binding cassette transporter A7 (ABCA7) has been identified as a susceptibility factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 63 publications
(67 reference statements)
3
81
0
1
Order By: Relevance
“…Studies in cell lines and mouse models suggest that a loss of ABCA7 function may have deleterious consequences for Aβ homoeostasis in the brain [12][13][14]. This is consistent with the previously reported significant association of ABCA7 SNPs with amyloid plaque load in human subjects [6].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Studies in cell lines and mouse models suggest that a loss of ABCA7 function may have deleterious consequences for Aβ homoeostasis in the brain [12][13][14]. This is consistent with the previously reported significant association of ABCA7 SNPs with amyloid plaque load in human subjects [6].…”
Section: Resultssupporting
confidence: 91%
“…In vitro studies revealed that ABCA7 transfection into cell lines constitutively expressing human amyloid-β precursor protein (APP) results in a significant reduction in production of amyloid-β peptide (Aβ) peptides [12], whereas siRNA-mediated knockdown of ABCA7 increased Aβ production under similar experimental conditions [13]. In addition, phagocytic clearance of oligomeric Aβ was found to be impaired in ABCA7-deficient macrophages compared with wild-type (WT) macrophages [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ABCA7 gene, which was also identified in the largest GWAS to date performed in African Americans [20], encodes a member of the superfamily of ATP-binding cassette (ABC) transporters which traffic substrates across cell membranes and are largely involved in lipid transport and homeostasis. ABCA7 has been shown to directly mediate phagocytosis, membrane trafficking of APP and amyloid processing [50]. CD33, also called Siglec-3, is a transmembrane glycoprotein expressed on myeloid progenitor cells, mature monocytes and macrophages, that contains an extracellular immunoglobulin (Ig) V-set sialic-acid binding domain, an extracellular Ig C2-set domain and cytosolic immunoreceptor tyrosine-based inhibitory motifs.…”
Section: Novel Susceptibility Loci Associated With Late-onset Admentioning
confidence: 99%
“…The reduced capacity of ABCA7-depleted macrophages to phagocyte Aβ and its microglial expression in the brain suggest a role in Aβ clearance [90,92,93] . Recently, a negative role in APP processing and Aβ production through endocytosis regulation has also been shown [94] . Whatever the pathway involved (Aβ clearance or production), loss of ABCA7 function may result in an increased charge of Aβ peptide in the brain.…”
Section: The Sorl1 Genementioning
confidence: 99%